Conceptual and Pedagogical Feasibility of KUKUSA Local Wisdom as Foundation for Contextual IPAS Teaching Materials Development - Kasmudin Mustapa; Vivin Elfitriyah Hs; Afadil; Siti Nuryanti; Ahmad Ramadhan (Universitas Pendidikan Ganesha, 2026)
This study investigates the feasibility of KUKUSA (Kukita Kutima Sampa) local wisdom as a foundation for developing IPAS teaching materials aimed at enhancing creative thinking and collaboration skills among elementary school students. Using a Research and Development (R&D) approach with the ADDIE model, this study focused on the Analysis and Development phases conducted at SD Inpres 1 Inti Bantaya, Parigi Moutong Regency, Central Sulawesi. Data were collected through classroom observation, in-depth interviews, document analysis, and expert validation. The learning needs analysis revealed a critical gap between Merdeka Curriculum demands and actual classroom practices IPAS instruction relied exclusively on generic textbooks with no local wisdom integration, leaving creative thinking and collaboration skills insufficiently facilitated. Expert validation of the developed teaching material, assessed across nine aspects by two specialist validators using a 1–4 Likert scale, produced an overall mean score of 3.66 (92%), categorized as Very Valid. The highest scores were recorded on Supporting Completeness (M = 3.88) and Local Wisdom Integration (M = 3.83), confirming that KUKUSA's ecological philosophy is authentically and substantively embedded across all material dimensions. The KUKUSA philosophy's communal, activity-based, and ecologically oriented nature provides natural scaffolding for all five creative thinking dimensions (fluency, flexibility, originality, elaboration, and harmony) and all five collaboration skill dimensions. These findings establish KUKUSA as both culturally legitimate and pedagogically valid as a foundation for contextual, 21st-century-oriented elementary science education.